Решите уравнения:а)(3х+1)^2-9(x+1)(x-1)=0б)одна девятая умножить на х^2=0,81
(3x+1)²-9(x-1)(x+1)=0
9x²+6x+1-9(x²-1)=0
9x²+6x+1-9x²+9=0
6x+9=0
6x=-9
x=-9/6
x=-1,5
1/9*x²=0.81
x²=0,81*9
x²=7,29
x₁=-2,7
x₂=2,7
a)(3х+1)^2-9(x²-1²)=09x²+6x+1-9x²-9=06x+10=0x=-10/6б)1/9* х^2=0,81
x^2=0.81*9
x^2=7.29
x(1)=2.7
x(2)=-2.7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(3x+1)²-9(x-1)(x+1)=0
9x²+6x+1-9(x²-1)=0
9x²+6x+1-9x²+9=0
6x+9=0
6x=-9
x=-9/6
x=-1,5
1/9*x²=0.81
x²=0,81*9
x²=7,29
x₁=-2,7
x₂=2,7
a)(3х+1)^2-9(x²-1²)=0
9x²+6x+1-9x²-9=0
6x+10=0
x=-10/6
б)1/9* х^2=0,81
x^2=0.81*9
x^2=7.29
x(1)=2.7
x(2)=-2.7